Caracterização textural dos sedimentos (subfundo raso) do canal do espadarte, Curuçá-Pará - SILVA, Paulo Victor Magno (2019)
The Espadarte Channel is located adjacent to the coastal line of Romana Beach in Guara Island, Curuça-PA, characterized by indented coastline, full of recesses where can be found a variety of estuaries (Franzinelli 1990). The general objective of this research was to contribute with a basic understand about The Espadarte Channel, describing the testimonies and texturally characterizing the surface sediments. The samples were subjected to particle size analysis, texture characterization and research about the organic matter content and calcium carbonate. The description and the particle size analysis of the testimonies shown a variation between the intervals (coarse sand to medium silt) generated mainly through the tide action, that contribute with the input of sediment and organic material mainly the ones from the Curuçá River estuary to The Espadarte Channel. The organic matter and CaCO3 kept a correlation with different particle size fractions, being the largest amounts of organic matter in sediments and CaCO3 higher in coarse sediments texturally the surface sediments of Espadarte Channel shown a perpendicular variation in relation to the channel, thicker sediments were found in the centre of the channel and thinner samples were found in points distal to the centre of the channel. According to Folk‟s texture classification the sediments ranged from thinner sand to coarse sand sediments showing sediments poorly selected to moderately selected with asymmetry varying from roughly symmetric and asymmetric very positive, which indicates that in the area there is predominance of sedimentation in the central portion of the channel and removal/disposal on the banks. In the Larsonneur distribution were found sediments type AL1 mainly on the deeper points and on the points where the bathymetric quotas were lower it was observe d that sediments surfaces are of type LL1. The Perjrup diagram classified the channel as high hydrodynamic (IV-A) on the central proportion of the channel and high (III-B) on the distal points